Repair of Spontaneous Left Atrial Dissection Resulting in Severe Paravalvular Native Mitral Valve Regurgitation - Eldridge, Tayler B. (JACC Case Rep, 2020)
A 54-year-old male with history of end-stage renal disease secondary to hypertension on hemodialysis with moderate aortic valve insufficiency presented with progressive exertional dyspnea and lower extremity edema over several weeks. Relevant history included hospitalization for Staphylococcus epidermidis bacteremia secondary to dialysis catheter line infection 6 months prior. (Level of Difficulty: Advanced.)